PENGANGKATAN ANAK INTERNASIONAL DI INDONESIA - Aminah, Aminah (Diponegoro Private Law Review, 2018)
Nowadays, the number of international adoption child has been increased and many people do not know about the regulation. This article wants to know the regulation, implementation and legal consequences of the international adoption child. Based on normative yuridical approach with analytical descriptive specification show that there are regulation concerning international adoption child which focuses on welfare and child protection aspects, while the implementation process can be done through 10 stages, and the legal effect of the international adoption is two namely the adoption  through a state court causing legal consequences of unlinking the relationship of adopted child with their biological parents, but adopted child also inherited from their adoptive parents, the emergence of custody rights and rights of alimentation. for the  adoption through the Religious court does not result in a new legal effect between an adopted child and an adoptive parent but only raises the rights of safeguarding and education for the adopted child and the will of the will for both. Keywords: adoption of child, International, Indonesia